SOSIALISASI PEMBERDAYAAN KEARIFAN LOKAL DALAM PROSES BELAJAR MENGAJAR BERBASIS ETNOSAINS BAGI GURU FISIKA DI SMA MUBTADIIN PAMEKASAN - Umamah, Chairatul; Andi, Herman Jufri (STAI Darul Qalam Tangerang, 2023)
Based on the results of observations made, information was obtained that teachers were less able to carry out a learning process that was in accordance with the demands of current developments in accordance with curriculum progress. Education plays a role not only as a means of transferring knowledge, but more broadly as an acculturator. The importance of innovation in learning in schools emphasizes the need for a responsive approach to local cultural riches and values. The local wisdom approach emerges as a promising paradigm, creating space for innovation to have a positive impact on learning activities. The lack of empowerment of local wisdom in teaching and learning activities by teachers in schools can cause a separation between curriculum content and students' daily lives. This can result in low student interest and motivation to learn. The aim of this community service activity is to offer innovative learning solutions through a local wisdom approach in the context of learning activities. This activity is carried out by providing socialization and assistance to physics teachers in a creative way by integrating local wisdom culture with science, so that it can have a positive impact on the learning process at school. It is hoped that innovative learning based on local wisdom will create an interesting learning environment and support children's development by enriching their experience of local wisdom values and traditions